Optimalisasi Budaya Sekolah Dalam Meningkatkan Perilaku Ramah Lingkungan Hidup di SMP Negeri 1 Lasem - Estu Budi Winarni, (Jurnal Bintang Pendidikan Indonesia, 2023)
Character is an attitude or behavior that is owned and attached to a person's personality. School as a place of learning and education can be used as a place to instill character in students. Through instilling school culture, it is hoped that the character of students can be formed. The problems at SMP Negeri 1 Lasem regarding the cultivation of this character are not optimal. Originally the person in charge of the character of the students was the 7K Team (Beauty, Discipline, Cleanliness, Health, Tidiness, Shade and Family) which consisted of 7 people. The reality that happened in schools was not optimal in enforcing 7K. The main cause was that the 7K team lacked cooperation in carrying out their duties. To overcome this, the school formed a School Culture Team consisting of 12 teams. The twelve teams include: Quality Culture Team, Healthy Culture Team, Clean Culture Team, Green Culture Team, Safe Culture Team, Religious Culture Team, Nationalist Culture Team, Independent Culture Team, Mutual Cooperation Culture Team, Integrity Culture Team, Discipline Culture Team and Literacy Culture Team. Each team has a program set out in the Guidebook. All programs are implemented and reported and evaluated. Coordination between teams is carried out routinely in each semester. The existence of this team was able to help shape the character of SMP Negeri 1 Lasem students in increasing environmentally friendly behavior to become more optimal. Furthermore, the final goal can be achieved, namely the formation of a school culture with character by realizing environmentally friendly behavior in schools.